Mapping the conceptual space formed by students' understanding of coordination number of a transition metal complex: an exploratory study. Issue 3 (20th June 2019) - Sreenivasulu, Bellam; Subramaniam, R.
Abstract : We report here on an exploratory study done with a sample of university students ( N = 140) which sought to explore their understanding of the term 'coordination number', a concept encountered in the topic of transition metals chemistry, through a simple open-ended question. The findings show that the conceptual space related to the conceptions students harbour span the interval from non-canonical to canonical limits. That is, the responses from the students include incorrect, partially correct and correct answers. Additionally, instructor commentary, based on teaching experience acquired with a number of cohorts of students, is provided for the range of conceptions encountered, a departure somewhat from the traditional approach, and among the very few, if any, studies, which use such an approach. Those conceptions that are partially correct cannot strictly be labelled as alternative conceptions as it is argued that these can still be used by students to solve problems set in certain contexts on the topic.